Validation study of synthetic models for esophageal atresia with tracheoesophageal fistula (EA/TEF): A simulation-based training in pediatric surgery - Zahradníková Petra; Hnilicová Silvia; Lindák Martin; Pechanová Rebeka; Števková Dominika; Vitovič Pavol; Laurovičová Miroslava; Horn František; Tvrdoň Tomáš; Babala Jozef (Journal of Pediatric Surgery Open)
Background: Pediatric surgery is a highly specialised field, with minimally invasive surgery (MIS) posing greater technical challenges than conventional open surgery. Proficiency requires both in and out-of-operating-room training, with simulation playing a crucial role. The purpose of this study was to explore MIS perceptions, training experiences, and preferences regarding laparoscopic simulation training. Furthermore, we aimed to validate two synthetic EA/TEF models. Method: A questionnaire focused on the degree of adoption of MIS among paediatric surgeons was proposed online to participants at the 68th Czech and Slovak Pediatric Surgery Congress in Slovakia in 2024. All participants also had scheduled sessions to practice advanced laparoscopic skills on two synthetic EA/TEF models. The purpose of this study was to analyse experiences with paediatric MIS, the implementation of simulation training, and personal stances on integrating simulation training into training curricula. EA/TEF models were validated with a 5-point Likert scale. Results: Thirty-three paediatric surgeons from 14 centres in two countries completed the questionnaire. Six (18 %) were novices, 12 (36 %) intermediate trainees, and 15 (45 %) specialists with over 11 years of practice. Eight participants (18 %) declared weekly access to simulation training, while 49 % had none. Additionally, 15 individuals (45.5 %) strongly agree and 48.5 % agree that regular training on simulators enhances surgical skills in MIS procedures in the operating room. Twenty-six respondents (76 %) believe that simulator training should be part of the requirements for pediatric surgical trainees, with no significant difference according to the surgeons' experience (p = 0.290). Thirty surgeons validated the EA/TEF models. Highest ratings were for overall impression and tool usefulness in experienced surgeons' training (mean scores: 4.5 and 4.6). The working space received the lowest score (mean: 3.6 ± 0.8), with experienced surgeons rating it significantly lower (3.4) than the inexperienced group (4.1, p = 0.030). No significant differences were observed between models in Likert scale parameters. Conclusion: Simulation training is essential for teaching MIS in paediatric surgery, improving skills, and should be part of specialisation preparation. Synthetic EA/TEF models received high ratings as effective training tools for thoracoscopic EA/TEF training. Further studies are needed to prove construct validity.